2002
DOI: 10.1002/jcp.10165
|View full text |Cite
|
Sign up to set email alerts
|

Polarized glucose transporters and mRNA expression properties in newly developed rat syncytiotrophoblast cell lines, TR‐TBTs

Abstract: In this study, we have established new syncytiotrophoblast cell lines (TR-TBTs) from the recently developed transgenic rat harboring temperature-sensitive simian virus 40 large T-antigen gene (Tg-rat). Four conditionally immortalized syncytiotrophoblast cell lines (TR-TBT 18d-1 approximately 4) were obtained from pregnant Tg-rats at gestational day 18. These cell lines had a syncytium-like morphology, could be prepared as monolayers, expressed cytokeratins and rat syncytiotrophoblast markers, and exhibited api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…11,14,19) Immunocytochemical studies showed that localization of GLUT1 and GLUT3 in TR-TBT 18d-1 and TR-TBT 18d-2 cells coincide well with those of rat SynI and SynII in vivo, respectively. 14,15) Therefore, we chose to use these cell lines to clarify the mechanism, physiological role and pharmacological significance of the polar distribution of membrane proteins in the syncytiotrophoblast.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…11,14,19) Immunocytochemical studies showed that localization of GLUT1 and GLUT3 in TR-TBT 18d-1 and TR-TBT 18d-2 cells coincide well with those of rat SynI and SynII in vivo, respectively. 14,15) Therefore, we chose to use these cell lines to clarify the mechanism, physiological role and pharmacological significance of the polar distribution of membrane proteins in the syncytiotrophoblast.…”
mentioning
confidence: 80%
“…14) To isolate total RNA from the TR-TBTs, cultures were incubated at 37°C on type I collagen-coated dishes (Asahi Techno Glass Co., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(75) The blood-placental barrier (BPB) Syncytiotrophoblast cell lines (TR-TBTs) (76) A syncytium-like morphology, carrier-mediated transport The cells from brain Neuronal cell line, N14.5. (77) from the suprachiasmatic nucleus Per1 and Per2, NMDA receptors Oligodendrocyte cell line (OLP6) (78) 2′-3′-cyclic-nucleotide 3′-phosphodiesterase, galactocerebroside Second endothelial differentiation gene receptor-2…”
Section: The Blood-cerebrospinal Fluid (Bcsfb) Barriermentioning
confidence: 99%